Spectrum of anemia after kidney transplantation: pathophysiology and therapeutic implications. Issue 10 (14th September 2016) - Bamgbola, Oluwatoyin F.
Abstract: The prevalence of anemia in the first month after transplant is 70%–80%. The rate declines to 30%–40% at 3 months and 20% by 12 months. Its occurrence is influenced by the quality of the transplanted organ, bone marrow regenerative capacity, amount of surgical blood loss, and increased iron recycling. There is also a blunted response by oxidative inflammation to the effectiveness of supranormal levels of erythropoietin (EPO) release during ischemic‐reperfusion allograft injury. The prevalence rate of late‐onset post‐transplant anemia (PTA) is 30%–50%. This category of patients falls into two ill‐defined groups: (i) those with impaired renal capacity for EPO synthesis and (ii) those with bone marrow resistance. Given the difference in pathophysiology, the current KDIGO guideline that adopts uniform therapeutic approach for the two groups may be inappropriate. Comorbidity due to iron deficiency is common. Anemia is predictive of cardiovascular morbidity and shorter graft survival. Perhaps due to concern for the safe use of EPO stimulating agent (ESA) to correct anemia, there is often inadequate treatment of late‐onset PTA. However, universal application of ESA may be harmful. Therefore, clinical trials are needed to define parameters for selecting patients (e.g., EPO assay) that will benefit the most from therapy for anemia.